Study on the mechanism of acupuncture to improve mild cognitive impairment in hypertension by regulating intestinal microbiome - Dong, Xinlei; Hao, Xiaomin; Wen, Jian; Yan, Qinfeng; Ma, Kaixuan; Liu, Qingguo; Li, Juan; Zhang, Lili (Frontiers in Neuroscience, 2024)
High blood pressure is a significant risk factor for cardiovascular diseases and is linked to an increased risk of mild cognitive impairment (MCI). The lack of effective treatments for these conditions highlights the urgent need for novel therapeutic approaches. Recent research suggests that the gut microbiota-brain-gut axis plays a crucial role in the pathogenesis of hypertension and MCI by regulating the nervous, endocrine, and immune systems. Acupuncture, an established therapeutic modality, has shown promise in influencing the course of hypertension and MCI by modulating the gut microbiota. This review aims to summarize the mechanistic relationships between the gut microbiome, hypertension, and MCI, and to explore the potential of acupuncture as a treatment strategy for managing Mild cognitive impairment in Hypertension concurrently.